Frequency of Fluoroquinolone and Aminoglycoside Resistance Online Probe Assay in Multidrug-Resistant Tuberculosis Patients - Qasim Nawaz, Sajjad Naseer, Imran Khan, Asad Ali, Akhlaq Ahmad, Aima Hameed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The resistance of tuberculosis to anti-tuberculous therapy is a severe public health concern all over the globe. The most common and important cause of resistance to anti-tuberculous therapy is poor patient compliance with or inappropriate therapy dosing. Objective: In order to evaluate the prevalence of resistance to commonly used 2nd-line anti-tuberculous drugs, an online probe assay was conducted among patients diagnosed with multi-drug-resistant tuberculosis. This study specifically focused on patients who were receiving treatment with fluoroquinolones and aminoglycosides and were seeking care at Lady Reading Hospital, a tertiary care facility located in Peshawar. Methods: This study was conducted at the Department of Pulmonology ward of Lady Reading Hospital, Peshawar, from Jan 2021 to Jan 2022, six months in which a total of 150 patients were observed to determine the frequency of common 2nd-line standard anti-tuberculous drugs resistance online probe assay in patients with multidrug-resistant tuberculosis. flouroquinolones and . Non-probability sequential sampling was the method used for sampling. Results: This study, conducted at the Department of Pulmonology ward of Lady Reading Hospital in Peshawar, employed a cross-sectional design. The objective was to assess the prevalence of resistance to standard 2nd-line anti-tuberculous drugs among patients with multidrug-resistant tuberculosis using online probe assays. A total of 150 patients were included in the analysis (n = 15-24). The age distribution of the participants was as follows: 52 patients (34.7%) were between 25-34 years old, 34 patients (22.7%) were between 35-44 years old, and 35 patients (23.3%) were between 45-54 years old (Table No. 1). The mean age was found to be 33.76 years, with a standard deviation of 16.42. In terms of gender, 66 patients (44%) were male and 84 patients (56%) were female (Figure No. 1). Sputum culture conversion at 2 months was observed in 50.7% of the cases, while it was absent in 49.3% (Table No. 3). Additionally, previous tuberculosis treatment was reported by 5 patients (0.7%), while the majority (99.3%) had no history of previous treatment (Table No. 6). Conclusion: The use of fluoroquinolones standard antia was the A considerable percentage of resistance was discovered in the nation’s first attempt to test the extent of 2nd-line medication resistance among MDR-TB isolates. Even though there were 84 females present, it’s interesting that none of the isolates fit the requirements for XDR-TB. A crucial indicator of the probable severe pan resistance development of XDR-TB is the use of first-line drugs. While the national TB control plans are put into place, MDR-TB cases must be closely monitored. The short: Regularity, proximity Keywords: 2nd-line standard anti-tuberculous drugs resistance, multidrug-resistant tuberculosis. Tuberculosis fluoroquinolones and aminoglycosides,